Takhrij and Syarah Hadith of Chemistry: The Benefits of Siwak and Chemical Ingredients for Dental Health - Rizky Dinda Islami; Raodatul Jannah; Wawan Hernawan; Mujiyo Mujiyo; Tety Sudiarti (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the benefits of miswak for dental health. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this of this study are the benefits of siwak content for maintaining healthy teeth. The conclusion of the research is takhrij and syarah hadith of the Prophet about the siwak plant which contains a lot of chemical substances in maintaining healthy teeth which has been done by the Prophet. This study recommends chemists to develop miswak content that is applied to maintain healthy teeth and gums.